Prevalence of multidrug resistant Acinetobacter baumannii in clinical samples in a tertiary care hospital - Sudhaharan, Sukanya; Vemu, Lakshmi; Kanne, Padmaja (International Journal of Infection Control, 2015)
Acinetobacter baumannii, most often multidrug resistant, is a difficult to treat pathogen particularly in intensive care units. The aim of this study is to determine the prevalence and increasing antibiotic resistance of A. baumannii isolates. A retrospective analysis of all patients, seeking medical assistance from our institute, between January to December 2014, from whom clinical specimens (excluding blood and urine) yielded A. baumannii was performed. A.baumannii was isolated from 227 clinical specimens (excluding blood and urine). About 90 (40%) of the A.baumannii were from tracheal aspirates, 47(20%) from purulent aspirates, 17 (7%) in sputum, 17 (7%) pleural fluid. Multi drug resistance was observed in 175 (77%) isolates and 30 (13%) were XDR (extensively drug resistant) being sensitive only to colistin. Strict adherence to hospital antibiotic policies and proper infection control measures helps to prevent the emergence of this pathogen.